2022
DOI: 10.3389/fonc.2022.948110
|View full text |Cite
|
Sign up to set email alerts
|

The role of fascin-1 in the pathogenesis, diagnosis and management of respiratory related cancers

Abstract: Human cancer statistics report that respiratory related cancers such as lung, laryngeal, oral and nasopharyngeal cancers account for a large proportion of tumors, and tumor metastasis remains the major reason for patient death. The metastasis of tumor cells requires actin cytoskeleton remodeling, in which fascin-1 plays an important role. Fascin-1 can cross-link F-actin microfilaments into bundles and form finger-like cell protrusions. Some studies have shown that fascin-1 is overexpressed in human tumors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 120 publications
(193 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have identified the role of fascin-1 in gynecologic cancers, 16 gastrointestinal cancers, 17 and respiratory-related cancers. 18 This review aims to elucidate fascin-1 expression in urologic cancers (bladder, prostate, and kidney cancers and adrenocortical carcinoma [ACC]) and the signaling mechanisms of the fascin-1 gene in these urologic cancers. In addition, we evaluate the potential of fascin-1 as a prognostic marker and a therapeutic target, to support further studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified the role of fascin-1 in gynecologic cancers, 16 gastrointestinal cancers, 17 and respiratory-related cancers. 18 This review aims to elucidate fascin-1 expression in urologic cancers (bladder, prostate, and kidney cancers and adrenocortical carcinoma [ACC]) and the signaling mechanisms of the fascin-1 gene in these urologic cancers. In addition, we evaluate the potential of fascin-1 as a prognostic marker and a therapeutic target, to support further studies.…”
Section: Introductionmentioning
confidence: 99%